Social history of an Indian caste: the kayasths of Hyderabad - Leonard, Karen Isaksan (Delhi Oxford University Press, 1978)
This book is a historical study of the kayasths of Hyderabad, who have adapted their occupational patterns and marriage alliances to changing political and economic conditions over 200 years. From the turbulent military campaigns of the eighteenth century to the bureaucratic modernization of the twentieth, the kayasths have employed diverse strategies to serve Hyderabad state. The book traces the structural relationships among some 320 patrilineages, combining Genealogical reconstructions with extensive research in private and official archives. The changing occupational, kinship, and marriage patterns challenge many assumptions about caste, Class, and social mobility in Indian society, revising the traditional belief that social mobility in India is significantly different from that in other systems of social stratification. The extent to which brahmanical ideas of Inheritance and marriage regulations influenced behavior is also questioned. The br>Epilogue to this third edition documents the recent changes and developments in the Mathur sub-caste, tracing its movement from a cosmopolitan post-mughal world to a cosmopolitan and global English-speaking world in the late twentieth and early twenty-first century. Social History of an Indian caste will interest students and scholars of anthropology, sociology, political Science and history.
Keywords: Sociology